The effectiveness of health systems in influencing avoidable mortality: a study in Valencia, Spain, 1975-90. Issue 3 (June 1996) - Albert, X; Bayo, A; Alfonso, J L; Cortina, P; Corella, D
Abstract : OBJECTIVES: To measure variations in the Holland and Charlton classifications of avoidable death causes and to estimate the effect of the Spanish national health system on avoidable mortality. DESIGN: Mortality in the Valencian Community was assessed between 1975 and 1990. The classifications of Holland and Charlton, used to assess avoidable causes of death, were compared. Holland's classification was then used to divide avoidable mortality into two groups–medical care indicators (MCI), which show the effectiveness of health care, and national health policy indicators (NHPI), which show the status of primary prevention. Comparisons were made with rates, group rates, and population rates. Trends and indices were also studied. SETTING: Valencia, Spain, 1975-90. RESULTS: During the study period, avoidable morality (only assessed by MCI) fell 63%, whereas the remainder of the mortality (non-MCI causes, that is all the non-avoidable causes together with the NHPI group) fell by 17%. If it is assumed that the mortality due to non-MCI causes indicates the overall effect of the environmental, social, nutritional, and genetic influences, then the difference between this and the MCI group would take us nearer the actual effect of the intervention of the health system. CONCLUSIONS: It is concluded that in this community, the health system has been responsible for approximately 47% of the total reduction in mortality from avoidable causes in the period studied.